EXTENSION PROJECT: CATARACT SURGERY IN A PRIVATE CLINIC IN ANÁPOLIS – GO (CIPEEX, 2025)
Cataract, an opacity of the crystalline lens causing visual impairment, is a global concern affecting millions of people, especially the elderly. Diagnosis involves detailed ophthalmologic examinations, such as ultrasound or optical biometry. Surgical removal of the opaque lens and implantation of an intraocular lens (IOL) are the definitive treatments. This study reports the experience of 13 medical, pharmacy, and nursing students from the Universidade Evangélica de Goiás who observed cataract surgeries during the first semester of 2023. They followed the surgical process, including anesthesia and the surgery itself, learning about neuroanatomy, pharmacology, and physiology. Data analysis was based on a qualitative approach, highlighting the importance of practical learning in healthcare education. This experience provided a rich learning environment and a deeper understanding of patient care, contributing to knowledge in the field of health and surgery. The study emphasizes the need for more cataract surgeries, highlighting the important role of the Brazilian Unified Health System (SUS) and the goal of eliminating blindness caused by this condition.
Keywords: Ophthalmologic surgical procedures; cataract; intraocular lenses; visual acuity